Effect of Ginger Essential Oil on in Vitro Gas Production, Rumen Fermentation and Methane Production - Önder Canbolat; Erdinç Altınçekiç; Şeniz Öziş Altınçekiç (Journal of Agricultural Sciences)
In this study, control (0), 50, 100, 200, 400, 800 and 1000 mg L-1 ginger essential oil (GEO) (Zingiber officinale Roscoe) was added to rumen liquid (RL). Then, the effects of the GEO added to the RL In vitro gas production, organic matter digestibility (OMD), metabolisable energy (ME), rumen fermentation parameters and methane (CH4) production were examined on these samples. It was determined that the addition of the GEO to RL decreased the in vitro gas production of Trifolium pratense hay (TPH), the OMD and ME contents, total volatile fatty acids (TVFA), acetic acid (AA), propionic acid (PA), butyric acid (BA) and other volatile fatty acids (OVFA) (P<0.05). Moreover, it was determined that while the productions of carbon dioxide (CO2), CH4 and ammonia nitrogen (NH3-N) decreased, the ratios of the rumen pH and AA/PA increased (P<0.05) depending on the increase in the dose of GEO. In conclusion, it was determined that the GEO dose which had the highest negative effect on the in vitro gas production, the rumen fermentation, the nutrient digestibility, the CH4 and the CO2 production was 1000 mg L-1. It was concluded that since high doses of GEO affect rumen fermentation and digestion of feeds negatively, it would be appropriate to use 200 mg L-1.